Penerapan Audit Kepatuhan dalam Mengatasi Risiko Kredit Macet pada PT Bank Perekonomian Rakyat Bina Usaha Dana Kabupaten Flores Timur (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to examine the implementation of compliance audit in addressing non performing loan risk at PT Bank Perekonomian Rakyat Bina Usaha Dana in East Flores Regency. The research method used in this study is descriptive qualitative with data collection techniques using observation, interviews, documentation, and literature review. The research informants were the compliance director, internal audit executive officer, compliance and risk management executive officer, credit department head, and two debtors. The research results indicate that the implementation of compliance audit has not been optimal because it does not use tools such as C2R for detecting credit applications and the application of the 7P principle has not been maximized in the prospect, payment, and profitability, so there are still non performing loans in quite large amounts.